Cryptogenic Ischemic Stroke in Migraine: Role of Patent Foramen Ovale - Gollion, Cédric; Lerebours, Fleur; Barbieux-Guillot, Marianne; Fabry, Vincent; Larrue, Vincent (Frontiers in Pain Research, 2022)
Introduction: Migraine with aura (MWA) has been associated with cryptogenic ischemic stroke (CIS) after adjustment for the presence of a patent foramen ovale (PFO) assessed by transcranial Doppler. This study aimed at evaluating the association of MWA with causal PFO assessed by Transesophageal echocardiography (TEE) in CIS. Methods: Patients aged 18-54 years consecutively treated for first acute ischemic stroke in a university hospital stroke unit, between January 2017 and December 2019, were included in this cross-sectional study. Associations between migraine subtypes and PFO were tested for all PFO, possibly causal PFO (PFO with large shunt and/or atrial septal aneurysm [ASA]), and the probably causal PFO subset (large shunt and/or ASA, plus risk of paradoxical embolism [RoPE] score ≥ 7). We adjusted the association between migraine subtypes and possibly causal PFO, which included the probably causal subset, for age, sex, large artery atherosclerosis and small vessel disease. Results: Two hundred and two patients with CIS were included of whom 42/202 (20%) had MWA, 32/202 (15%) had migraine without aura and 128/202 (63%) had no migraine. MWA was associated with possibly causal PFO (OR = 4.0, 95%CI [1.78 – 9.3], P < 0.001) and with probably causal PFO (OR = 5.4, 95%CI [2.37 – 13], P < 0.001). In a multinomial logistic regression analysis MWA remained associated with possibly causal PFO (OR = 3.24, 95% CI [1.45 – 7.2], P = 0.004). Conclusion: In a young adult population with CIS, MWA was strongly associated with possibly causal PFO, ie. with large shunt or combined with interatrial septal aneurysm.